Formulating Business Strategy in O'Corner (The Indonesian Journal of Business Administration, 2015)
O’Corner is a small-medium enterprise based in Indonesia that has a core business in serving healthy snack and dessert with unique packaging to its customer. This business was established since 2013. The development in food and beverage industry in Indonesia is growing rapidly and it affect O’Corner in sales. The stagnant sales and lacked of spaces to stores the stock in O’Corner made the owner have to think a suitable strategy to apply. Strategic formulation process done through the three stages of analysis, the input phase, analysis, and decision stages. The final stage is a case analysis to formulate a decision to be taken. The decision was based on justification pedestal made qualitatively and quantitatively, structured or unstructured, so that a decision can be taken significantly with existing conditions. The results of this research are recommending the business strategy with market penetration, the author give an action plan for the next 5 years in order to make O’Corner more grow up and better than the other competitor. Keywords: business strategy, snack business, business model canvas